UTILIZATION OF UNMANNED AERIAL VEHICLE (UAV) FOR MEASUREMENT OF SURFACE COAL MINING SITUATION - Kurniawan, Sigit; Cahyadi, Mokhamad Nur (Journal of Marine-Earth Science and Technology, 2022)
The rapid development of technology has given rise to innovations and new ways of solving problems. One of them is measuring the situation of surface coal mines. So far, measurements have been made using a Laser Scanner. However, now the Unmanned Aerial Vehicle (UAV) can replace it by considering the aspects of work safety, effectiveness, and efficiency in the field. This study analyzes the influence of the distribution of Ground Control Points (GCP). It compares the measurement method using a Laser Scanner with a UAV in a surface coal mine situation. In addition, this study aims to determine the exact parameters regarding the distribution and number of control points in using UAVs to measure surface coal mining situations. The results showed that the UAV could be used to measure the situation of surface coal with the results of the acquisition parameter research following the 1:1000 PERBIG scale tolerance map, with a tolerance value of <10 cm and the volume difference between the Laser Scanner and UAV is 0.131%. Regarding time analysis and work safety, measurements using UAVs can measure surface mining situations for ± 40 minutes. In addition, personnel do not need to approach the measurement object, so it is better than measurements using a Laser Scanner.